The Bacterial Flagellar Type III Export Gate Complex Is a Dual Fuel Engine That Can Use Both H(+) and Na(+) for Flagellar Protein Export - Minamino, Tohru (PLoS Pathog, 2016)
The bacterial flagellar type III export apparatus utilizes ATP and proton motive force (PMF) to transport flagellar proteins to the distal end of the growing flagellar structure for self-assembly. The transmembrane export gate complex is a H(+)–protein antiporter, of which activity is greatly augmented by an associated cytoplasmic ATPase complex. Here, we report that the export gate complex can use sodium motive force (SMF) in addition to PMF across the cytoplasmic membrane to drive protein export. Protein export was considerably reduced in the absence of the ATPase complex and a pH gradient across the membrane, but Na(+) increased it dramatically. Phenamil, a blocker of Na(+) translocation, inhibited protein export. Overexpression of FlhA increased the intracellular Na(+) concentration in the presence of 100 mM NaCl but not in its absence, suggesting that FlhA acts as a Na(+) channel. In wild-type cells, however, neither Na(+) nor phenamil affected protein export, indicating that the Na(+) channel activity of FlhA is suppressed by the ATPase complex. We propose that the export gate by itself is a dual fuel engine that uses both PMF and SMF for protein export and that the ATPase complex switches this dual fuel engine into a PMF-driven export machinery to become much more robust against environmental changes in external pH and Na(+) concentration.